Identify Tcea3 as a novel anti-cardiomyocyte hypertrophy gene involved in fatty acid oxidation and oxidative stress - Guo, Yingying; Cen, Xian-feng; Li, Dan; Qiu, Hong-liang; Chen, Ya-jie; Zhang, Meng; Huang, Si-hui; Xia, Hao; Xu, Man (Frontiers in Cardiovascular Medicine, 2023)
Background: Chronic pressure overload triggers pathological cardiac hypertrophy that eventually leads to heart failure. Effective biomarkers and therapeutic targets for heart failure remain to be defined. The aim of this study is to identify key genes associated with pathological cardiac hypertrophy by using bioinformatics analyses. Methods: Comprehensive bioinformatics tools were used to screen genes related to pressure overload-induced cardiac hypertrophy. We identified differentially expressed genes (DEGs) by overlapping three Gene Expression Omnibus (GEO) datasets (GSE5500, GSE1621, and GSE36074). Correlation analysis and BioGPS online tool were used to detect the genes of interest. A mouse model of cardiac remodeling induced by transverse aortic constriction (TAC) was established to verify the expression of the interest gene during cardiac remodeling by RT-PCR and western blot. By using RNA interference technology, the effect of TCEA3 silencing on PE-induced hypertrophy of neonatal rat ventricular myocytes (NRVMs) was detected. Finally, gene set enrichment analysis (GSEA) and the online tool ARCHS4 were used to predict the possible signaling pathways, and the fatty acid oxidation relevant pathways were enriched and then verified in NRVMs. Finally, MitoSOX staining was used to detect the effect of TCEA3 on mitochondrial oxidative stress, and the contents of NADP(H) and GSH/GSSG were detected by relevant kits. Results: A total of 95 DEGs were identified and TCEA3 was negatively correlated with Nppa, Nppb and Myh7. The expression level of TCEA3 was downregulated both in vivo and in vitro. Knockdown of TCEA3 aggravated cardiomyocyte hypertrophy induced by PE in NRVMs. GSEA and online tool ARCHS4 predict TCEA3 involved in fatty acid oxidation (FAO). Subsequently, RT-PCR results showed that knockdown of TCEA3 up-regulated ces1d and pla2g5 mRNA expression levels. TCEA3 silencing resulted in an increase in mitochondrial ROS, and a decrease in the rate of GSH/GSSG and NADPH/NADP+ in vitro cardiomyocyte hypertrophy. Conclusion: Our study identifies TCEA3 as a novel anti-cardiac remodeling target by regulating FAO and governing mitochondrial oxidative stress.